Contribution de la méthode de prospection éléctrique à l'étude hydrogeologique de la région de Jerba Midoun - Rouissi, Ghada; Jallouli, Chokri (Faculté Des Sciences de Tunis, 2004)
Keywords: Géologie – Djerba

Ranking suitable sites for Soil Aquifer Treatment in Jerba Island (Tunisia) using remote sensing, GIS and AHP-multicriteria decision analysis - Anane, Makram; Kallali, Hamadi; Jellali, Salah; Ouessar, Mohamed (International Journal of Water, 2008)
The present study aims to locate and rank suitable sites for Soil Aquifer Treatment (SAT) in Jerba Island (South Tunisia) by integrating a single-objective AHP method into a GIS model. The methodology represents a first step in SAT basin construction projects before field investigations. It considers several criteria related to technical, environmental and cost aspects. The result showed that a large area, covering 1489 ha, is suitable for SAT, which exceeds the required area to infiltrate the total treated wastewater produced by all the island wastewater plants. Being situated inside agricultural areas and near coastlines, potential sites for SAT could increase groundwater availability for irrigation and also mitigate existing marine intrusion problem facing Jerba aquifer. The best sites are found closer to Aghir plant than the rest of island WWTPs.
Keywords: Géologie – Djerba

Détermination des argiles de potiers par méthode électrique : les argiles de Guellala - Tlet au sud de l’île de Djerba - Khalifa, Fahem; Ben Dahman, Abderrazak; Jouirou, Mohamed (2009)
Keywords: Géologie – Djerba

Sédimentologie et géochimie des Dépôt littoraux quaternaires: reconstitution des variations des climats et du niveau marin dans le sud est tunisien - Jedoui, Younes (Université de Tunis II, 2000)
Keywords: Géologie – Djerba

L’île de Djerba (Tunisie) et le développement durable : une vision de géographe - Paskoff, Roland (Géographie, 2004)
Keywords: Géologie – Djerba

L’érosion des côtes : Le cas des plages de l’île de Jerba (Tunisie) - Paskoff, Roland (Houille blanche, 2004)
Keywords: Géologie – Djerba

L’érosion de l’île de Djerba en Tunisie - Kaib, Nadia (Université Paris 12, 2006)
Keywords: Géologie – Djerba

Soil Aquifer Treatment Areas in Tunisia: Jerba Island - Anane, Makram; Kallali, Hamadi; Jellali, Salah; Ouessar, Mohamed (Wastewater Reuse–Risk Assessment, Decision-Making and Environmental Security, 2007)
Soil aquifer treatment (SAT) has been practiced in various dry land and semiarid areas as means to reduce environmental risk by improving wastewater quality at disposal sites and to replenish aquifers enabling the use of reclaimed water for nonrestrictive crop irrigation. SAT success is preconditioned by an appropriate site selection, a correct design, and a continuous maintenance. The location of the SAT basins is determined by a multitude of criteria often less than inituitive. This study aims to identify potential sites for SAT in Jerba Island integrating geographic information systems (GIS) tools and the analytical hierarchy process (AHP).
Keywords: Géologie – Djerba